The future of Erdoğan and the AKP. (2nd January 2016) - Yeşilada, Birol A.
ABSTRACT: Turkish politics is complex and, at times, comes close to being bizarre. When the Justice and Development Party ( Adalet ve Kalkınma Partisi [AKP]) came to power it embarked on ambitious economic and political reforms that at last promised to bring embedded democracy to Turkey. Yet, since 2007, most of the initial reforms have regressed, deepening societal cleavages that threaten the stability of the country, and a popularly elected president threatens to change the parliamentary democratic system with an autocratic presidential order. While the AKP can celebrate in its unprecedented four election victories since 2002, its recent actions should give concern to anyone who cares about the future of Turkey.